Overuse elbow injuries in youth gymnasts - Bonazza, N. A.; Saltzman, E. B.; Wittstein, J. R.; Richard, M. J.; Kramer, W.; Riboh, J. C. (The American Journal of Sports Medicine, 2021)
Background: Gymnastics is a unique sport that places significant loads across the growing elbow, resulting in unique overuse injuries, some of which are poorly described in the current literature.